DAMPAK SISTEM OLAH TANAH DAN MULSA TANDAN KOSONG KELAPA SAWIT TERHADAP PERTUMBUHAN, HASIL JAGUNG MANIS (Zea mays saccharata) DAN TATA AIR TANAH - Andreas Junico Marulitua Situmorang; Bandi Hermawan; Hesti Pujiwati (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2019)
[IMPACT OF THE TILLAGE SYSTEM AND OIL PALM EMPTY FRUIT BUNCH MULCH ON GROWTH, YIELD OF SWEET CORN (Zea mays saccharata) AND GROUNDWATER SYSTEM]. This study aims to determine the impact of land management and the use of oil palm empty fruit bunches (TKKS) mulch. This research was conducted from August to October 2018, arranged in a split plot design with two factors. As a first factor, land management consists of unprocessed, plowed, and plowed and harrowed. The treatment of oil palm empty fruit bunches mulch as the second factor consisted of no mulch, 9 tonnes/ha of mulch, 12 tonnes/ha of mulch, and 15 tonnes/ha of mulch. Plant variables observed consisted of plant height, stem diameter, number of leaves, fresh plant weight, plant dry, ear weight, ear length, ear diameter. Soil variables observed were the redistribution of groundwater and infiltration. The results showed no significant interaction between the tillage system and the application of oil palm empty fruit bunch mulch on all observed variables. Treatment without tillage or mulch dose of 12 tons/ha can provide growth and yield of sweet corn plants better than other treatments. The highest water content and infiltration rate were obtained from the dosage of oil palm empty bunches mulch 15 tons/ha. Soil cultivation by plowing and harrowing produces the highest infiltration rate compared to lower tillage intensities. About 18% to 42% of the diversity of growth and yield of sweet corn plants have a significant relationship with the diversity of groundwater.